THE INFLUENCE OF ENVIRONMENTAL ENTREPRENEURSHIP LEVEL AND ENTREPRENEURIAL CHALLENGES ON THE INNOVATION OF WOMEN ENTREPRENEURS - Sriayudha, Yayuk; Musnaini, Musnaini; Roza, Suswita (Journal of Business Studies and Management Review, 2023)
Entrepreneurship plays a pivotal role in a nation’s economic development, and it is essential for women to participate and innovate in this sphere actively. This study seeks to investigate and delineate the following: (1) the correlation between the degree of entrepreneurship, entrepreneurial challenges, the entrepreneurial environment, and the innovation of female entrepreneurs; (2) the interplay between the level of entrepreneurship, entrepreneurial challenges, and the innovation of female entrepreneurs, with the entrepreneurial environment acting as a mediating factor; and (3) the framework of entrepreneurial innovation specific to female entrepreneurs. This research focuses on female entrepreneurs engaged in eco-friendly business practices in the Jambi Province, involving a sample of 200 respondents. A nonprobability sampling technique was employed to select participants. Data collection was carried out using a structured questionnaire. The gathered data was analysed using the Structural Equation Model (SEM/PLS) via the Smart PLS tool. The findings reveal significant links between the degree of entrepreneurship and the entrepreneurial environment, as well as between entrepreneurial challenges and both the entrepreneurial environment and eco-friendly entrepreneurial innovation. The primary goal is to develop an empirical model of eco-friendly entrepreneurial innovation, which can be utilised to promote environmental sustainability by integrating key factors identified in the current study. This research is anticipated to make a significant theoretical contribution to scholars in related fields.